2017
DOI: 10.1093/jcr/ucx120
|View full text |Cite
|
Sign up to set email alerts
|

That’s Not How I Remember It: Willfully Ignorant Memory for Ethical Product Attribute Information

Abstract: This research documents a systematic bias in memory for ethical attribute information: consumers have better memory for an ethical attribute when a product performs well on the attribute versus when a product performs poorly on the attribute. Because consumers want to avoid emotionally difficult ethical information (e.g., child labor) but believe they should remember it in order to do the right thing, the presence of negative ethical information in a choice or evaluation produces conflict between the want and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 73 publications
3
42
0
Order By: Relevance
“…Although there are hints in the literature that hypocrisy could influence ethical consumption (Carrington et al 2016;Gamma et al 2018), our findings offer a new explanation for the relationship between proximity dimensions and consumer FT engagement. This is in line with the arguments of Reczek et al (2017), who found that people wilfully ignore information about ethical attributes to avoid emotionally difficult ethical information (e.g., child labor, exploited marginalized farmers) in purchase decisions, suggesting that wilfully ignorant memory is a more morally acceptable form of coping with 'want/should' conflict. In doing so, people stray from embedded beliefs and behavior to satisfy the want self's desire to feel good, even though they may be physically, socially or psychologically proximate to the marginalized producers/workers (Hassan et al 2016).…”
Section: Footnote 3 (Continued)supporting
confidence: 86%
“…Although there are hints in the literature that hypocrisy could influence ethical consumption (Carrington et al 2016;Gamma et al 2018), our findings offer a new explanation for the relationship between proximity dimensions and consumer FT engagement. This is in line with the arguments of Reczek et al (2017), who found that people wilfully ignore information about ethical attributes to avoid emotionally difficult ethical information (e.g., child labor, exploited marginalized farmers) in purchase decisions, suggesting that wilfully ignorant memory is a more morally acceptable form of coping with 'want/should' conflict. In doing so, people stray from embedded beliefs and behavior to satisfy the want self's desire to feel good, even though they may be physically, socially or psychologically proximate to the marginalized producers/workers (Hassan et al 2016).…”
Section: Footnote 3 (Continued)supporting
confidence: 86%
“…The mechanisms responsible for motivated forgetting may, under some circumstances, enable people to forget undesirable details of past actions (Anderson & Hanslmayr, 2014). And people tend to forget the unethical actions of third parties when they benefit from those actions (Bell, Schain, & Echterhoff, 2014;Reczek, Irwin, Zane, & Ehrich, 2017). It is possible, therefore, that our memory for some moral violations could tap into these self-serving biases and thus reduce the accuracy of recollections for certain details.…”
Section: Discussionmentioning
confidence: 99%
“…As individuals in the sample recalled their enjoyment at the time of purchase as being reduced over time, their likelihood of upgrade increased. There might be motivated reasoning effects at play (Kunda, 1990;Reczek, Irwin, Zane, & Ehrich, 2018), causing individuals to misremember past enjoyment to justify the upgrading behavior, along the lines of those reported…”
Section: Open Accessmentioning
confidence: 92%
“…Motivation comprises any wish, desire, or preference that concerns the outcome of a reasoning task (Kunda, 1990). One example of motivated reasoning is the willfully ignorant memory effect reported by Reczek, Irwin, Zane, and Ehrich (2018), whereby consumers present better memory for an ethical attribute when a product performs well on that attribute versus when a product performs poorly on that same attribute. Specifically, consumers systematically forget or misremember negative ethical attribute information when they face the conflict between their in the moment desire to avoid negative ethical information and their general long-term belief that they should be morally good.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation